Self-Routing For Optical Burst Switched Networks - Mellah, H.; Abbou, F. M.; Abid, A. (2005)
Optical urst Switching (O S) has received considerable attention in the past few years, and various solutions have been proposed and analyzed in an attempt to improve its performance. In O S, the control packet and the corresponding data burst are launched at the source at time instants separated by an offset. The control packet contains information re uired to route the data burst through the optical transmission core, the length of the burst, and the offset value, and it is sent over an out-of-band control channel (wavelength). Furthermore, the O S nodes need this offset time to setup their switches fabrics so that the data burst can cut through without the need for any buffers. The determination of this offset is a key design feature of all O S networks, and its effectiveness is measured in terms of the burst loss probability. However, using a long offset time will result in a longer end-to-end latency, which is not desirable in such systems. In this paper, we propose to integrate the self-routing scheme to the O S in order to decrease the control packet processing time, which results in decreasing the offset time.